2015
DOI: 10.1002/fsn3.264
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, antioxidant, and antibacterial properties of pomace extracts from four Virginia‐grown grape varieties

Abstract: Grape pomace is a potential source of natural antioxidant and antimicrobial agents. Phenolic compounds, antioxidant, and antibacterial properties of pomace extracts from four Virginia‐grown grape varieties were investigated. White grape pomaces had higher (P < 0.05) solvent extraction yield than red varieties. Concentrations of total phenolic (TPC), total flavonoid (TFC), total anthocyanin (TAC), tannins, condensed tannins (CT), as well as antioxidant capacities (DPPH• and ABTS•+free radical scavenging) differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 39 publications
10
105
4
1
Order By: Relevance
“…The negative associative effects by presence of compound as phenols (not measure in this experiment) could be affected the efficiency on the energy use. Xu et al (2016) reported an average concentration of 102 mg phenolic/kg of red grape pomace, and the anti-nutritional effects of phenolic compounds are well known (Waghorn and McNabb 2003). The above could be supported by previous findings (Bahrami et al 2010, Nistor et al 2016 in which it was observed that intake of DGP increased beyond 10% while feed efficiency of lambs was notably decreased.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…The negative associative effects by presence of compound as phenols (not measure in this experiment) could be affected the efficiency on the energy use. Xu et al (2016) reported an average concentration of 102 mg phenolic/kg of red grape pomace, and the anti-nutritional effects of phenolic compounds are well known (Waghorn and McNabb 2003). The above could be supported by previous findings (Bahrami et al 2010, Nistor et al 2016 in which it was observed that intake of DGP increased beyond 10% while feed efficiency of lambs was notably decreased.…”
Section: Methodssupporting
confidence: 69%
“…Some studies on the use of grape pomace as an ingredient for ruminant rations reported poor results on animal performance (Manterola et al 1997, Nistor et al 2016 and those results have been associated to the type of DGP, because DGP commonly used was a by-product of the alcoholic fermentation, and therefore it was low in sugars and energy value. The unfermented by-products of viticulture have a greater concentration of sugars, and theoretically more energy concentration (Baumgärtel et al 2007), however, they maintain higher concentrations of the original compounds such as tannins and phenols (Xu et al 2016), which may represent negative associative effects with other components of the diet that could affect the feeding value. Therefore, it is possible that the expected feeding value of GP could be decreased as its inclusion increases in the diet.…”
Section: Introductionmentioning
confidence: 99%
“…Such increasing interest is justified by the rich diversity of bioactive compounds found in these by‐products (Elkhatim, Elagib, & Hassan, ; Igual, García‐Martínez, Camacho, & Martínez‐Navarrete, ; Lafka et al, ). Thus, their properties and potential as food supplements have been extensively studied (Shahidi & Ambigaipalan, ; Xu, Burton, Kim, & Sismour, ). In this context, the bioactive compounds found in grape pomace/extract/products have been evaluated in terms of their nutraceuticals properties, as well as extensive searchers for scientific evidence of their performance as low‐density lipoprotein oxidation inhibitors, antimutagenics, antivirals, anti‐tumorals, and in chemoprevention by inhibiting reactions that increase the risk of coronary heart disease, reducing significant and harmful forms of several diseases, and neutralizing and/or preventing degenerative processes such as cancer, cardiovascular diseases, diabetes, oxidative stress skin damage, and others (Gül, Acun, & Sen,¸ H., Nayir, N., & Türk, S., ; Vodnar et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids have a planar structure with hydroxyl groups and double bond in position C2-C3, which give them capacity as a chelators, free radical scavengers and inhibitors of enzymes that produce free radicals [37]. It is known that secondary metabolites, such as alkaloids, flavonoids, tannins and other phenolic compounds are responsible of antioxidant and antimicrobial activities in most plants [38]. Oxidative stress is one of the main pathological mechanisms by which the parasite produces severe damage to the host, therefore, the antioxidant capacity of the HlMeOHe, could explain, at least in part, the beneficial effects showed in the treated mice.…”
Section: Discussionmentioning
confidence: 99%